Vliv subjektivních stylotvorných faktorů na styl současných českých odborných textů: k vývojovým proměnám stylu současných českých teoreticky odborných textů - Schacherl, Martin (Stylistyka, 2021)
The aim of this study is to demonstrate the impact of subjective stylistic factors on the style of contemporary theoretical professional communication written in the Czech language. The paper presents the quantitative characteristics of selected expressional means used in contemporary Czech written scientific discourse through analysing representative material from selected monographs produced in the selected areas of scientific domains. The research material base comprised a corpus of current Czech theoretical-scientific monological communication amounting to 5,000 pages. The corpus included collective or single-author monographs, thematically divided into five groups of fields recognised by the Czech Science Foundation (hereinafter GAČR) as: (1) technical sciences (1TEXT1, 1TEXT2, 1TEXT3); (2) sciences of inanimate nature (2TEXT1, 2TEXT3); (3) medical and biological sciences (3TEXT1, 3TEXT2); (4) humanities and social sciences (4TEXT1, 4TEXT2); (5) agricultural and biological[1]environmental sciences (5TEXT1, 5TEXT2, 5TEXT3). The term “contemporary scientific communication / contemporary scientific discourse” is understood as scientific monological Czech monographical communication produced approximately within the last 15 years. The proper aim of our study is to verify through sufficiently conclusive material whether contemporary Czech written theoretical scientific monological communications feature any differences that hold across diverse scientific fields, which would result from subjective stylistic factors. The analysis of selected expressional components in the corpus did confirm the (certifiable) occurrence of subjective stylistic factors in contemporary Czech theoretical discourse, yet present to a very limited extent. Individual differences were mostly manifesting in the representation of foreign words, rhetorical questions, platitudinous or rhetorical means of expression and also in expressing similarity. The biological factors, i.e. the author’s age and sex and the stylistic opposition of collective v. single-author monograph were not evidenced in the examined textual corpus. The most conspicuous differences between the analysed monographs resulted from the field affiliation of particular monographs, namely from (dis)respect for the ruling communicative norms in the given field/s.